Exposure to dust and rat urinary aeroallergens in research establishments. Issue 9 (September 1994) - Nieuwenhuijsen, M J; Gordon, S; Tee, R D; Venables, K M; McDonald, J C; Newman Taylor, A J
Abstract : As part of an epidemiological study rat urinary aeroallergen (RUA) and total dust concentrations were measured at three research establishments. Personal RUA measurements in nine exposure groups over a workshift showed highest exposure for animal technicians (geometric mean (GM) = 32.4 micrograms/m3) and lowest for workers in slide production and office (GM > or = 0.1 micrograms/m3). Except for slide production workers, contact with rats, their tissues, faeces, or urine comprised less than half the work shift. Exposure during contact with rats was considerably higher. Personal RUA measurements in nine task categories showed high RUA concentrations for handling rats (GM = 68.0 micrograms/m3) and cleaning out (GM = 53.6 micrograms/m3). Traces of RUA could still be measured in tearooms inside and near offices outside the animal houses. Total dust concentrations were low.